(untitled) (European Bison Conservation Newsletter, 2008)
Summarised is very interesting and almost unknown source, documenting first years of E. bison introduction to Bieszczady. The chronicle stored at Forestry Widełki was sawed from the fire that destroyed the building. In this document given are exact days of bison arrival, names of people who participated in the event, and described are 2 first years of bison acclimatisation and the period just after their release to the wild.